THE INFLUENCE OF FISCAL CAPACITY, IHDI AND UMP ON ECONOMIC GROWTH IN JAVA ISLAND IN THE PERSPECTIVE OF ISLAMIC ECONOMICS - Marfilia, Alda; Abdul Ghofur, Ruslan; Nurmalia, Gustika (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to examine the influence of fiscal capacity, Islamic Human Development Index and Provincial Minimum Wage on economic growth. This study uses quantitative methods with Vector Error Correction Mode (VECM) analysis techniques. The population in this study were six provinces on the island of Java from 2008-2023 which were taken by saturated sampling method. The results showed that partially in the long term and short term fiscal capacity and Provincial Minimum Wage have a significant positive effect on economic growth. while the Islamic Human Development Index (IHDI) variable has no significant effect on economic growth. While simultaneously fiscal capacity, Islamic Human Development Index affects economic growth. The implications of this research are expected to be useful for various groups. for regulators in the six provinces on the island of Java which are sampled can be one of the references in determining policies. For academics, it is expected to be useful for the development of science and for the community, it is hoped that it can be an addition to information and literacy.